O Poder Constituinte Derivado e os Direitos Fundamentais: uma análise acerca da constitucionalidade da Emenda Constitucional n. 95/16 - Gonçalves, Allan Alexandre Mendes (2018)
The Constitutional Amendment n. 95/2016, established a new fiscal regime for Brazilian government expenditures. Over a period of 20 years, the budget at the federal level may not contain expenses higher than the values observed in the previous year, as adjusted by the HICP. The same criterion was adopted to update the minimum spending on health and education, which ceased to be directly linked to the Net Current Income for the year, as previously foreseen in the constitution, which is equivalent to establishing a reduction of the minimum expenditure required to guarantee these rights fundamental rights. This research had as main objective to verify if the changes imposed by Constitutional Amendment n. 95 violate the commitment to preserve and expand fundamental rights instituted by the Constituent Originator of the Brazilian Constitution of 1988. The analysis was based on bibliographical research, having as sources specialized doctrine, technical publications and jurisprudence on the subject. At first, based on the absolute and relative theories of fundamental rights, it was analyzed whether the constituent derived, with the amendment, would contradict the originating constituent power, being the conclusion by the unconstitutionality. Next, it was assessed whether this unconstitutionality could be overcome taking into account the parameters of the jurisprudence of the crisis, a theory derived from the precedents created in the European Constitutional Courts in the crisis period. It was concluded that the measure violates the essential core of fundamental rights, offending the constitutional text, and Article 110 of the Temporary Provisions Act (ADCT), which provides for changes in minimum expenditures on education and health, must be declared unconstitutional.